The Roman Villa in Rabaçal and Álvaro Siza - João Pedro Xavier (2011)
The residential area of the Roman villa in Rabaçal is a rare example of a house with an octagonal peristyle remarkable by its design coherence at all architectural levels, from the overall scale to decorative motifs. Everything is regulated by proportions derived from its octagonal plan naturally based in ad quadratum geometry. Recently, Siza was challenged to design covers and a visit tour in order to preserve this invaluable patrimony. Quite aware of the quality of the architecture displayed in this Roman villa he must have recognized in-situ many of his own architectural concerns. The sketchbook was opened, and the drawing search led him to propose two wood rectangular grid covers which, in spite of their modernity and technical sophistication, are still shapes with formal affinities with each part of the villa.